Growth Differentiation Factor-15 (GDF-15) Levels Are Associated with Cardiac and Renal Injury in Patients Undergoing Coronary Artery Bypass Grafting with Cardiopulmonary Bypass - Kahli, Abdelkader (Public Library of Science, 2014)
OBJECTIVE: Growth differentiation factor-15 (GDF-15) has been identified as a strong marker of cardiovascular disease; however, no data are available concerning the role of GDF-15 in the occurrence of organ dysfunction during coronary artery bypass grafting (CABG) associated with cardiopulmonary bypass (CPB). METHODS: Five arterial blood samples were taken sequentially in 34 patients from anesthesia induction (IND) until 24 h after arrival at the intensive care unit (ICU). Plasma levels of GDF-15, follistatin-like 1 (FLST1), myeloperoxidases (MPO), hydroperoxides and plasma antioxidant status (PAS) were measured at each time-point. Markers of cardiac (cardiac-troponin I, cTnI) and renal dysfunction (neutrophil gelatinase-associated lipocalin, NGAL) and other classical biological factors and clinical data were measured. RESULTS: Plasma GDF-15 levels increased gradually during and after surgery, reaching nearly three times the IND levels in the ICU (3,075±284 ng/L vs. 1,061±90 ng/L, p<0.001). Plasma MPO levels increased dramatically during surgery, attaining their highest level after unclamping (UNCLAMP) (49±11 ng/mL vs. 1,679±153 ng/mL, p<0.001) while PAS significantly decreased between IND and UNCLAMP (p<0.05), confirming the high oxidative status induced by this surgical procedure. ICU levels of GDF-15 correlated positively with cTnI and NGAL (p = 0.006 and p = 0.036, respectively), and also with hemoglobin and estimated glomerular filtration rate (eGFR). Among all the post-operative biomarkers available, only eGFR, NGAL and GDF-15 measured at ICU arrival were significantly associated with the onset of acute kidney injury (AKI). Patients with a EuroSCORE >3 were shown to have higher GDF-15 levels. CONCLUSIONS: During cardiac surgery associated with CPB, GDF-15 levels increased substantially and were associated with markers of cardiac injury and renal dysfunction.